Legal forms of implementation of foreign tax policy in the context of European integration of Ukraine - Латковська, Тамара Анатоліївна; Латковська, Т. А.; Латковская, Тамара Анатольевна; Latkovska, Tamara A.; Чайка, Вікторія Вікторівна; Чайка, В. В.; Чайка, Виктория Викторовна; Chaika, Viktoriia V.; Касьяненко, Любов Михайлівна; Касьяненко, Л. М.; Касьяненко, Любовь Михайловна; Kasianenko, Liubov M.; et al. (ASERS Publishing, 2019)
The article defines the basic legal forms of implementation of the foreign tax policy of Ukraine. Particular attention is paid to characterizing the features of the EU tax policy. The assessment of the current state of approximation of the Ukrainian tax legislation to the EU standards is based on the legal analysis of the provisions of the Association Agreement between Ukraine and the EU and other regulations. The issue of approximation of the Ukrainian tax legislation to the acquis communitaire in the field of energy taxation has been updated. The legal forms of tax cooperation between Ukraine and the OECD are analyzed. The following areas of Ukraine's foreign tax policy are emphasized: joining the BEPS Action Plan and the Multilateral Convention to Implement Tax Treaty Related Measures to Prevent Base Erosion and Profit Shifting. The legal description of certain provisions of bilateral agreements of Ukraine with the EU Member States and OECD in the area of avoiding double taxation of income and property is provided. On this basis, the conclusion is made about the decisive role of the contractual legal form in the process of implementing the foreign tax policy of Ukraine.

У статті визначено основні правові форми реалізації зовнішньої податкової політики України. Особливу увагу приділено характеристиці особливостей податкової політики ЄС. Оцінка сучасного стану наближення податкового законодавства України до стандартів ЄС базується на правовому аналізі положень Угоди про асоціацію між Україною та ЄС та інших нормативних актів. Актуалізовано питання наближення податкового законодавства України до acquis communitaire у сфері оподаткування енергії. Проаналізовано правові форми податкової співпраці між Україною та ОЕСР. Виділяють такі напрямки зовнішньої податкової політики України: приєднання до Плану дій BEPS та Багатосторонньої конвенції щодо впровадження заходів, пов'язаних із угодою про оподаткування, для запобігання розмиванню бази та переміщенню прибутку. Надано правове тлумачення окремим положенням двосторонніх угод України з державами-членами ЄС та ОЕСР у сфері уникнення подвійного оподаткування доходів та майна. На підставі цього робиться висновок про вирішальну роль договірно-правової форми у процесі реалізації зовнішньої податкової політики України.
Chaika V. V. Legal forms of implementation of foreign tax policy in the context of European integration of Ukraine / V. V. Chaika, L. M. Kasianenko, T. A. Latkovska, N. Y. Pryshva, V. V. Topchii // Journal of Advanced Research in Law and Economics. – Vol. 10 (1). - ASERS Publishing, 2019. - Р. 85-103.
Keywords: OECD; foreign policy; Monetary Union; Association Agreement with the EU for Ukraine; processes of harmonization; ОЕСР; зовнішня політика; валютний союз; Угода про асоціацію України з ЄС; процеси гармонізації; Research Subject Categories::LAW/JURISPRUDENCE